Autophagy Regulates the Post-Translational Cleavage of BCL-2 and Promotes Neuronal Survival - Laura Lossi; Graziana Gambino; Chiara Salio; Adalberto Merighi (The Scientific World Journal)
B-cell lymphoma 2 protein (BCL-2) is one of the more widely investigated anti-apoptotic protein in mammals, and its levels are critical for protecting from programmed cell death. We report here that the cellular content of BCL-2 is regulated at post-translational level along the autophagy/lysosome pathways in organotypic cultures of post-natal mouse cerebellar cortex. Specifically this mechanism appears to be effective in the cerebellar granule cells (CGCs) that are known to undergo massive programmed cell death (apoptosis) during post-natal maturation. By the use of specific agonists/antagonist of calcium channels at the endoplasmic reticulum it was possible to understand the pivotal role of calcium release from intracellular stores in CGC neuroprotection. The more general significance of these findings is supported by a very recent study Niemann-Pick transgenic mice.